Transvaginal partial excision of a circumferential urethral leiomyoma: Surgical technique and outcome - Leanne Brechtel; Joanna Orzel; Yiqin Xiong; Annah Vollstedt (Urology Case Reports)
We present a rare case of a 68-year-old female with urinary retention and a peri-urethral mass. The patient, with a history of thoracic aortic aneurysm, was referred to urology after a urethral mass was incidentally detected on CT imaging during aneurysm surveillance. Pelvic MRI identified a 4.8 cm circumferential, enhancing mass along the proximal urethra. A transvaginal ultrasound-guided biopsy confirmed a low-grade smooth muscle neoplasm, consistent with leiomyoma. The mass was successfully excised via a transvaginal approach. This case highlights the importance of a broad differential in female urinary retention and demonstrates the feasibility of vaginal excision for peri-urethral masses.